Retropharyngeal and parapharyngeal abscess in children. Retrospective study of 5 years in Pediatric Hospital of Coimbra - Ribeiro, Diana Cunha (2013)
Introduction: The retropharyngeal and parapharyngeal abscess are rare and potentially fatal infections, particularly in children.Material and methods: We conducted a retrospective study of patients diagnosed with retropharyngeal and parapharyngeal abscess, between June 2007 and June 2012, in a tertiary pediatric hospital. Proceeded to clinical files, with analysis of the following data: age, sex, initial symptoms, duration of symptoms, physical examination, laboratory tests and imaging, treatment, length of stay and complications.Results: We diagnosed 5 parapharyngeal abscess and three retropharyngeal abscess in the study period. The median age at presentation was 5 years old. There was a predominance of females (62,5%). The most common symptoms at initial clinical presentation were fever (62,8%), stiff neck (37,5%) and odynophagia (37,5%). Computerized tomography with contrast was performed in all patients. All patients received medical treatment. Three patients (37,5%) underwent surgical drainage and 5 patients (62,5%) received only medical treatment. There was no significant difference between the duration of hospitalization in those who underwent surgery alone or conservative treatment.Conclusion: Many patients with retropharyngeal and parapharyngeal abscess can be successfully treated with antibiotics and steroids, without resorting to surgery, with he latter being reserved for complications or unfavorable clinical course. The computerized tomography are important in the diagnosis and assessment of the extent of the infection, but are not always 100% valid for diagnosing abscess.